Rancang Bangun Sistem Kontrol Keasaman Air Kolam Ikan Menggunakan Sensor pH Berbasis Arduino - Gunadi; Muhammad Daud (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
Good water quality, especially the level of acidity greatly affects the success of fish farming. Water that is too acidic can cause slow growth and even lead to the death of fish. To measure and control the acidity of water, a tool that can work automatically is needed. For this reason, this study aims to design and build an automatic fish pond water acidity control device. This tool works by reducing some of the water and replacing it with new water. The components used include a 12 volt DC water pump, pH sensor, ultrasonic sensor, Arduino Uno, relay, and water reservoir. From the test results, it is found that the system can work well where the water pH value is 5.5 the system is able to increase it to 6.4 by reducing some of the water and filling it with water with a higher pH value of 8.3. Likewise, when the pH value of the water is 8.3, the system is able to reduce it to 7.6 by reducing some of the water and filling it with water with a pH value of 6.0.